Peer Review Committee Meeting, General Assembly and international Symposium of ABEST21 - Sorooshian, Shahryar; M., Waris; Senthil Kumar , T.; Hasahudin, Hassan; Ida Rizyani, Tahir; Nor Sofea, Iman (FIM-UMP, 2016)
On Tuesday, March 1, 2016, Dr. Mohd Ridzuan bin Darun, Dean, Faculty of Industrial Management, En. Hanafiah, Deputy Dean of FIM and Dr Puteri Fadzline, Head of MBA program, attended the Peer Review Committee at Sony University, Sony Corporation, Tokyo, Japan